Nodal Brillouin-zone boundary from folding a Chern insulator - Lang, Li-Jun (2018)
A Chern insulator is a building block of many topological quantum matters. Here, we discuss a nonsymmorphic Chern insulator, which preserves the nonsymmorphic symmetry and breaks the time-reversal symmetry. It consists of two half-filled Chern insulators, and the bulk energy spectrum is obtained from folding that of either Chern insulator. Such folding gives rise to a nodal boundary of the Brillouin zone, which is protected by the nonsymmorphic symmetries and other lattice symmetries of the system. It also provides one a natural platform to explore the non-Abelian Berry curvature and the resultant quantum phenomena. Moreover, the interplay between nonsymmorphic symmetries and the broken time-reversal symmetry leads to intriguing properties absent in ordinary Chern insulators. An additional degree of freedom, the parity of the nonsymmorphic symmetry, needs to be introduced for describing the topological pumping.